2016
DOI: 10.1016/j.ejmech.2016.06.016
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and biological evaluation of isomeric methoxy substitutions on anti-cancer indolyl-pyridinyl-propenones: Effects on potency and mode of activity

Abstract: Certain indolyl-pyridinyl-propenone analogues kill glioblastoma cells that have become resistant to conventional therapeutic drugs. Some of these analogues induce a novel form of non-apoptotic cell death called methuosis, while others primarily cause microtubule disruption. Ready access to 5-indole substitution has allowed characterization of this position to be important for both types of mechanisms when a simple methoxy group is present. We now report the syntheses and biological effects of isomeric methoxy … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 28 publications
(22 citation statements)
references
References 41 publications
1
21
0
Order By: Relevance
“…In a previous study, we found that indolyl pyridinyl propenones related to 6-MOMMIP caused cell rounding, surface blebbing and tubulin depolymerization within 4 h [27]. Likewise, we found that cell rounding and blebbing are early effects of 6-MOMIPP [28]. These features are consistent with the effects of direct microtubule depolymerizing agents.…”
Section: -Momipp Causes Microtubule Depolymerization By Targeting Thsupporting
confidence: 85%
“…In a previous study, we found that indolyl pyridinyl propenones related to 6-MOMMIP caused cell rounding, surface blebbing and tubulin depolymerization within 4 h [27]. Likewise, we found that cell rounding and blebbing are early effects of 6-MOMIPP [28]. These features are consistent with the effects of direct microtubule depolymerizing agents.…”
Section: -Momipp Causes Microtubule Depolymerization By Targeting Thsupporting
confidence: 85%
“…Follow-up structure–activity relationship (SAR) studies defined key features associated with three phenotypic classifications, namely, the induction of methuosis, vacuolization without cell death, 6 and disruption of microtubules leading to apoptosis. 7 Selected substitutions on the indole at position 2 or moving the methoxy group from position 5 to 6 8 redirected the mode of cytotoxicity from distinctive methuosis to microtubule disruption with little observable effect on vacuoles. However, the protein target(s) of the compounds that prompt the methuosis phenotype have not been identified.…”
Section: Introductionmentioning
confidence: 99%
“…It is reported that para positioning of nitrogen in the pyridinyl moiety of chalcones is vital for vacuolization, which is abolished when the nitrogen was at the meta position [6]. In addition, positioning of the methoxy group at the fifth position of indole in indolyl-pyridinyl-propenone analogs induced methuosis, while shifting the methoxy group to the sixth position abolished methuosis and disrupted microtubules in GBM cells [16]. Similarly, 2 of the iodoindoles (5-iodoindole and 7-iodoindole) have elicited vacuoles in nematodes.…”
Section: Vacuolar Death In a Nematode Modelmentioning
confidence: 99%